Response of fatal landslides to precipitation over the Chinese Loess Plateau under global warming - Guan, Xiaodan; Sun, Wen; Kong, Xiangning; Zhang, Fanyu; Huang, Jianping; He, Yongli (Frontiers in Earth Science, 2023)
Loess is sensitive to water, and rain-induced loess landslides are especially prevalent in the Chinese Loess Plateau (CLP). Some became fatal landslide disasters, leading to numerous casualties and significant socioeconomic losses. Extreme precipitation is the main cause of landslide occurrence. During the period 2004-2016, fatal landslides in CLP increased at a rate of 0.6 per year, with frequent landslide events occurring especially in the central and southwestern parts of CLP. It shows that SDII (simple daily intensity index) and R×5day (max 5-day precipitation amount) show a spatial distribution that is consistent with fatal landslides. Extreme precipitation events are frequent after 2000, and several extreme precipitation indices show an increasing trend with a higher magnitude than before 2000. In particular, in 2013, when the number of fatal landslides was as high as 17, SDII, R95pTOT (extremely wet days), R25mm (very heavy precipitation days) and R×5day all showed an abrupt increase. Single continuous precipitation events have a profound effect on fatal landslides. The study shows that single continuous precipitation events with cumulative precipitation of 185-235 mm and duration of 6 days or more have the highest correlation with fatal landslides. As the increasing occurrence of effective rainfall events induced fatal landslides by the global warming, it has to face more fatal landslides over CLP in the future, especially in the high emission scenario of Green House Gases (GHGs).